The Notch ligand Delta-like 4 (DLL4) as a target in angiogenesis-based cancer therapy? - Brzozowa, Marlena; Wojnicz, Romuald; Kowalczyk-Ziomek, Grażyna; Helewski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2013)
Angiogenesis is a complex multistep process by which new capillary structur-es arise from pre-existing vessels in response to angiogenic stimuli. This process plays a key role during tumorigenesis because the vascular network within the tumor enables malignant cells to establish distant metastases. Thus, it is not surprising that targeting tumors with angiogenesis-based therapy remains a significant area of preclinical and clinical studies. One of the most prominent factors considered as a promising target in such therapy is the Notch ligand Delta-like 4 (DLL4). Emerging evidence suggests that blockade of DLL4 in tumors results in excessive but non-productive angiogenesis which affects tumor growth, even in tumors which are insensitive to anti-VEGF therapy. Nevertheless, the careful evaluation of adverse effects on normal organs’ physiology in relation to therapeutic doses of DLL4 inhibitors will be critical for advancement of DLL4 blocking agents in clinical practice.